Inovasi Sistem Informasi Digital Berbasis Web Untuk Optimalisasi Pembayaran Tagihan Air Layanan Desa - Muhammad Saiful; Aswian Editri Sutriandi; Yupi Kuspandi Putra; L M Samsu (Fakultas Teknik Universitas Hamzanwadi, 2026)
This study focuses on the development of a web-based digital information system to optimize the water bill payment process for village water services at Bumdes Saling Sedok, Peresak Village. The manual system that has been used to date has led to various challenges, such as payment delays, recording errors, and a lack of transparency. Therefore, innovations based on information technology are expected to overcome these problems while improving service quality. The research methodology involves user requirements analysis, system design using a prototyping approach, and the implementation of web-based technology. The software used in the design and implementation of the system includes XAMPP as the web server, phpMyAdmin as the database, and Visual Studio Code as the text editor for developing PHP and HTML files. The developed system provides key features such as real-time access to billing information, online payment facilities, automatic notifications to customers, and financial reports for administrators. The expected outcomes include improved efficiency and effectiveness of the payment process, enhanced transparency of financial data, and easier access to services for the community. In addition, this system supports the empowerment of Bumdes through more modern and professional management. The main contribution of this research is the provision of a technological solution that not only improves the operational performance of Bumdes but also empowers the community to adopt technology for everyday needs. These findings can serve as a foundation for the development of similar systems in other regions, supporting digital transformation and enhancing community-based public services.